Analisis kesehatan bank dengan menggunakan metode RGEC pada bank umum syariah di Indonesia - Maria ulfa; Muhammad Salman; Mayang Murni (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to determine the health level of Islamic banks at Islamic Commercial Banks using the RGEC method, which includes Risk Profile, Good Corporate Governance, Earning (Rentability) and Capital (Capital). This study uses a quantitative method sourced from secondary data from Islamic Commercial Bank financial reports for 2015-2022. The data analysis used to determine the health level of banks in this study is descriptive analysis using the RGEC method. The results of the study show that the health level of Islamic Commercial Banks for 2015-2022 is at a composite rank of 1 (PK - 1), which is included in the "Very Healthy" category. The assessment of the health level of Islamic Commercial Banks for the 2015-2022 period on the Risk Profile factor using the NPF ratio is ranked 1 in the very healthy category. The assessment of the health level of Islamic Commercial Banks for the period 2015-2022 on the GCG (Good Corporate Governance) factor using the Self Assessment ratio is ranked 2 in the healthy category. The assessment of the health level of Islamic Commercial Banks for the period 2015-2022 on the Earning (Profitability) factor using the ROA ratio is ranked 1 in the very healthy category. The assessment of the health level of Islamic Commercial Banks for the period 2015-2022 on the capital factor (capital) using the CAR ratio is ranked 1 in the very healthy category.